Strawberry Cultivar Evaluations in Florida: 2006-07 Season - Bielinski M. Santos; Craig K. Chandler; Stephen M. Olson; Teresa W. Olczyk (EDIS, 2008)
HS1120, a 4-page fact sheet by Bielinski M. Santos, Craig K. Chandler, Stephen M. Olson, and Teresa W. Olczyk, presents the results of a study comparing cultivar performance in multiple locations throughout Florida. Includes references. Published by the UF Department of Horticultural Sciences, October 2007.